Ambient air pollution and the susceptibility to develop pulmonary tuberculosis: a multi country ecological study - K., Renuka; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis remains a major global health problem with 10.4 million incident cases in 2016. Although Mycobacterium tuberculosis is the causative agent, many environmental factors play a role in disease progression. Several respiratory hazards including smoking and indoor air pollution were suggested to increase the risk of tuberculosis, but only fewer studies has been conducted on the association between ambient air pollution and tuberculosis. Methods: Data on ambient air quality levels (annual mean concentration of particulate matter 2.5 µg/m3) for the year 2016 was collected from the World Health Organization (WHO) data base for 190 countries which comprises of 6 WHO regions. Similarly data on incidence and mortality rate of tuberculosis for the year 2016 was collected for the above countries from the WHO data base. The data were tabulated and statistical analysis was performed using Pearson’s correlation coefficient model to examine the association of annul mean concentration of particulate matter 2.5 with incidence and mortality rates of tuberculosis. Results: Incidence and mortality rates of tuberculosis were found to be increasing with increasing levels of air pollution. It was correlated using scatter plot. Pearson’s correlation coefficient for air pollution level and incidence of tuberculosis was 0.331 (95% CI: 0.435-0.883), (p<0.001), and for tuberculosis mortality was 0.39 (95% CI: 0.525-0.906) (p<0.001). Conclusions: The study suggests there is a significant positive relationship between ambient air pollution level and tuberculosis incidence and mortality rates.